The Practice of the “Inclusive Care Policy” of Mohism - Herranz Martín, Manuel (Sinología hispánica. China Studies Review, 2018)
This paper aims at contextualizing historically some parts of the Mò biàn, the dialectical part of the Mòzǐ, attributed to the later mohist school or Neo-Mohism. We will try to get a deeper understanding of two texts by linking them with the world view and circumstances of the time.Before going into those texts, first we will briefly review some aspects of today´s interpretation of the Mohist doctrine and compare the experience of the Mohism in China with its Western counterparts, the Cynic and Stoic Schools of Thought, since both shared Cosmopolitanism at the core of their doctrines. We will conclude that the circumstances preventing the implementation of Cosmopolitanism or the Universal Love policy as proposed by the mohists have been removed by the globalization allowing the possibility of this policy to be carried out.